2022
DOI: 10.1155/2022/7944063
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of the Traditional Chinese Medicine Treatment (HuoxueHuayu Therapy) for Malignant Tumors: A Systematic Review and Meta-Analysis

Abstract: Background. A malignant tumor is one of the refractory diseases that threaten human life and health. HuoxueHuayu therapy (one of the Traditional Chinese Medicine therapies to promote blood circulation and remove blood stasis) is widely used as an antitumor supplementary method. However, its efficacy and safety are still controversial. Therefore, the objective of this study was to provide evidence-based evidence for HuoxueHuayu therapy in the treatment of malignant tumors and confirm its safety and effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…[ 10 ], which typically represents Huoxuehuayu therapy, one of the TCM therapies to promote blood circulation and remove blood stasis. In the previous study [ 11 ], we demonstrated that Huoxuehuayu therapy showed promise in cancer treatment, improving quality of life, addressing cancer-related symptoms, and reducing toxicity in a secure way. However, it is unsure that the secure dosage of herbs or prescription with Huoxuehuayu functions .…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ], which typically represents Huoxuehuayu therapy, one of the TCM therapies to promote blood circulation and remove blood stasis. In the previous study [ 11 ], we demonstrated that Huoxuehuayu therapy showed promise in cancer treatment, improving quality of life, addressing cancer-related symptoms, and reducing toxicity in a secure way. However, it is unsure that the secure dosage of herbs or prescription with Huoxuehuayu functions .…”
Section: Introductionmentioning
confidence: 99%